Estrutura e funcionamento de ensino e a gestão educacional: avaliação de disciplinas em cursos de pedagogia e licenciatura na Universidade Federal do Ceará - Mendes, Debora Lucia Lima Leite (2011)
The main purpose of the current research was to accomplish an investigation about the conception of professors, students and graduates of Universidade Federal do Ceará (UFC) – who occupied administration positions in educational institutions in Fortaleza-CE at the time – referring the quality of teaching-learning process of the disciplines of the area of Elementary Education Structure and Operation, presented obligatorily for the courses of Pedagogy and other licentiates, because of their importance for the exercise of teaching as well as for the exercise of functions related do the education administration. Specifically, this study aimed: i) evaluating and pointing out possible modification needs in those disciplines to better discuss the articulation presented by theory and practice as well as contributing for the improvement of the teaching-learning process in Higher Education; ii) identifying pedagogic strategies that can contribute to the evolution and improvement of the referred disciplines; iii) identifying the necessary and indispensable competences to the graduates, specifically to those who will exercise functions related to School Administration; iv) achieving an historical evaluation about the importance of the disciplines of the area and justifying their relevance for courses of Formation of Teachers, exploring political and legal aspects; v) supplying subsidies to the courses of Pedagogy and other licentiates of UFC related to the curriculum/program of the disciplines, intending to provide another meaning to the contents and prioritizing the necessary competences and practical experiences that can contribute to successful pedagogic and professional practices. The importance of this study remains in its innovative character and pioneering nature in evaluating the disciplines that comprehend the area of studies in reference. The specialized literature refers to education public policy as well as the education legislation and it approaches themes as evaluation, history and education administration. Thus, a qualitative and quantitative research was accomplished, as a case study. The universe of this research is constituted by 05 (five) effective and temporary teachers who taught the disciplines of the area at the time; 167 (one hundred and sixty seven) students regularly registered in those disciplines and 10 (ten) graduates. The procedures were systematic and the collection of data accomplished through questionnaires applied in the beginning and at the end of the semester of the year 2010.1. Among other relevant aspects, this research verified that an initial formation with only a theoretical nature, can contribute, certainly, for the professional practice, but it is not capable of modifying pedagogical practices toward a quality administration. Therefore, a list of essential competences was made, to be used as parameter for the formation of futures education managers as well as suggestions about the need of modifications in pedagogic and methodological areas.